STUDI KEANEKARAGAMAN DAN KONDISI TEMPAT TUMBUH KANTONG SEMAR (NEPENTHES SPP) DI KAWASAN DANAU SEBEDANG KECAMATAN SEBAWI KABUPATEN SAMBAS - Dino, .; Astiani, Dwi; Kartikawati, Siti Masitoh (JURNAL HUTAN LESTARI, 2016)
Nepenthes spp is one of plant species that protected in its natural habitat as population continues decreasing.In West Kalimantanits population is found only in some places for example in the lake Sebedang Sambas district. This study aimed to determine diversity and site conditions in the lake region. The study was conducted using multifle plots technique that were purposive sampling. Results show that there were 3 species of Nepenthes Â found; Nepenthes mirabilis ( Lour ) Druce , Nepenthes gracilis Korth , and Nepenthes neglecta. Among three diferent sites condition (shrubs,open area and secondary lowland forest) two common species found ,yet only in shrubs area Nepenthes neglecta was found. Keywords : Nepenthes, diversity, habitat